Occurrence of Shiga toxin-producing Escherichia coli (STEC) in Brazil and its public health importance - Caldorin, Marielle (2013)
Shiga toxin-producing Escherichia coli (STEC) is a pathogenic bacteriuminvolved in outbreaks of foodborne illness, becoming a major public healthchallenge. This study aimed to report the occurrence of STEC in Brazil and itsimportance in public health, through a retrospective study that tried this pathogenlaboratory findings in reports involving animals, foods and humans. The positivity of STEC in cattle assessed in studies ranged from 1.4 to 71%. Non-O157 strains were predominant in all states, and the O157:H7 isolated from animals in the states of Rio de Janeiro, São Paulo and Paraná. In the state of SãoPaulo was isolated from 16 serotypes not found in other states. The positivity ofSTEC in different animal food sources, and water for human consumption fromthe state of São Paulo, Tocantins and Rio Grande do Sul ranged from 0 to 18.1%,observing 7 different serotypes. STEC O157: H7 was isolated from ground beefin São Paulo-SP. The positivity of STEC from the few studies in humans inBrazil, restricted to the states of São Paulo and Rio Grande do Sul, demonstratedlevels of isolation between 0.6 and 6.3%, 10 different serotypes were isolated,predominantly O111:NM. Although the incidence of human infection withSTEC in Brazil is relatively low, we observed a high prevalence of these bacteriain cattle and sheep, and the correlation of serotypes isolated from animals withfood and human isolates. Therefore the importance of good handling practices ofthe producer and the consumer to prevent possible food contamination.